Investigating the effects of ceramide and sphingomyelinase on the NMDA receptor of hippocampal pyramidal cell - Köker, Fatma Tuğba. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
Ceramide is a structural membrane component which plays important roles in carrying the message about the fate of cell such as apoptosis, di erentiation or cell growth. Also, hippocampus is a very important region for transferring the information in central nervous system and NMDA receptors are related with learning and memory. Various pathological conditions occur as a result of di erences in neuronal activities in hippocampus. Therefore, in this study, the e ects of C2-ceramide (10 M), C2- dihydroceramide (10 M) and sphingomyelinase (30 mU/ml, 50 mU/ml) on NMDA receptors of hippocampal CA1 pyramidal neurons were investigated by using the patchclamp technique. It was observed that C2-ceramide had a depression e ect on NMDA currents. C2-dihydroceramide, which is the inactive form of C2-ceramide, depressed the amplitude of NMDA currents, as well. In addition to that, sphingomyelinase which activates the formation of ceramide applied at two di erent concentrations. Both of them decreased the amplitude of NMDA current, so they had the same e ect as C2-ceramide. Besides being a second messenger in the cell, C2-ceramide and also C2- dihydroceramide may have some modulatory e ects on the cell membrane. Therefore, it is possible that sphingomyelinase interacts with the cell membrane directly to form ceramides. In conclusion, ceramide molecule plays an important role in the regulation of glutamate mediated NMDA currents which plays important roles in hippocampal plasticity, where clari cation of its role requires further investigations.|Keywords: C2-ceramide, C2-dihydroceramide, sphingomyelinase, hippocampus, NMDA currents, patch-clamp technique.
Keywords: Ceramides.; Niemann-Pick diseases.; Hippocampus (Brain); Methyl aspartate.; Patch-clamp techniques (Electrophysiology)